Operational and Microscopic Analysis for Public Transport –Case Study: Lattakia City, 8th of Adhar Street- - رستم اكرم; خيربك جميل (Latakia University Journal -Engineering Sciences Series, 2021)
Public transportation is one of the most important travel mode that used to make the movement of people in cities. Therefore, work is being taken to give priority to public transport buses, which is a supportive policy for transportation, which may give positive results, according to the various realistic conditions, including traffic and road conditions. A set of standards that ensure traffic priority used in many city streets to ensure the efficiency and reliability of vehicle movement during congestion periods and thus reaching lower flight time and lower cost. Reaching the required standards can require engineering change in the road segment or monitoring and controlling traffic signals. This study introduces traffic preference standards for transit buses in Syrian cities and provides some amendments to them to ensure better flow of traffic. 8th of Adhar Street in Lattakia Governorate was taken as a model for conducting this study, which initially included collecting engineering information (street length - number of lanes - width of lanes) and traffic information (general traffic statistics at peak hour - number of bus lines operating on this street - number of buses - travel time for each bus - bus frequency). A microscopic analysis of this data performed according to HCM2010, a microscopic analysis process based on the PTV VISSIM program and obtaining mixed transport traffic assessment and especially the evaluation of public bus traffic.